Local Government Policy in Improving the Quality of Islamic Religious Education in Bogor Regency - Muwafiqoh, Arisatul; Fauzan, Fauzan; Shidiq, Sapiudin (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to examine the policies of the Bogor Regency Government in improving the quality of Islamic Religious Education (PAI) in schools. This research uses a descriptive qualitative method with an empirical approach. The object of this research is the policies in Bogor Regency, and the research instrument is a human instrument. This study uses document data collection techniques and interviews. The analytical method used is the policy analysis method. The result showed that the policies of the Bogor Regency Government in improving the quality of PAI were contained in the Bogor Regency Regional Regulation Number 3 of 2021 concerning Amendments to Regional Regulation Number 4 of 2019 concerning the Bogor Regency Regional Medium Term Development Plan for 2018-2023. There are three policies, they are the Bogor Ngaos policy, adding four (4) hours of PAI subjects, increasing the welfare of educators and education personnel through giving allowances for honorary PAI teachers, and the Teacher Professional Education Program (PPG) by using the Regional Revenue and Expenditure Budget (APBD) of Bogor Regency. These policies have a positive impact and strengthen the students' character, which finally will improve the quality of PAI in Bogor Regency.